Intra- and inter-brand color differences of denture teeth under different illuminations - Nick POLYCHRONAKIS; Panagiotis LAGOUVARDOS; Gregory POLYZOIS; Hien Chi NGO (University of São Paulo, 2020)
Abstract Debonding, staining and wear are usually the reasons for denture teeth replacement by new ones from same or different brands. Objective This study investigates the possible differences in color of denture teeth of the same or different brands under different illuminations, since their metameric behavior in color under specific illumination may become unacceptable. Methodology For the purpose of this study, 10 denture teeth (#11), shade A3, of 4 different brands were selected (Creopal/KlemaDental Pro, Executive/DeguDent, Cosmo HXL/DeguDent, Ivostar/Ivoclar-Vivadent). Teeth stabilized in white silicone mold and the CIELAB color coordinates of their labial surface under 3 different illumination lights (D65, F2, A) were recorded, using a portable colorimeter (FRU/WR-18, Wave Inc). ΔE*ab values of all possible pairs of teeth of the same brand (n=45) or pair combinations of different brands (n=100) under each illumination light, in a dry and wet state were calculated. Data were analyzed statistically using 3-way ANOVA, Friedman's and Wilcoxon's tests at a significance level of α=0.05. Results The results showed that brand type affected significantly L*, a* and b* coordinates (p<0.0001), illumination a* and b* coordinates (p<0.0001), but none of them was affected by the hydration state of teeth (p>0.05). Intra-brand color differences ranged between 0.21-0.78ΔΕ* units with significant differences among brands (p<0.0001), among illumination lights (p<0.0001) and between hydration states (p=0.0001). Inter-brand differences ranged between 2.29-6.29ΔΕ* units with significant differences among pairs of brands (p<0.0001), illumination lights (p<0.0001) and hydration states (p<0.0001). Conclusions Differences were found between and within brands under D65 illumination which increased under F2 or A illumination affected by brand type and hydration status. Executive was the most stable brand than the others under different illuminations or wet states and for this reason its difference from other brands is the lowest. In clinical practice, there should be no blending of teeth of different brands but if we must, we should select those that are more stable under different illuminations